Analisis Kevalidan dan Kepraktisan Flipbook Digital Petualangan Literasi Nusantara pada Pembelajaran Unsur Intrinsik SD - Karisma Budy Ramadhani; Nurul Istiq’faroh; Maura Adien Nasywa Hamidiah; Dewi Aprillya (CV. Kurnia Grup, 2026)
Students’ reading literacy skills in elementary schools are still relatively low, which is partly caused by the use of less varied and less engaging learning media, resulting in low student involvement in the learning process. Therefore, innovative learning media are needed to improve students’ interest and understanding, especially in analyzing intrinsic elements of stories. This study aims to analyze the validity and practicality of a digital Flipbook learning media based on North Sumatran folklore in Indonesian language learning at the elementary school level. This study employed a mixed methods approach that combines quantitative and qualitative data. The research subjects consisted of one teacher as a media expert validator to assess the validity aspect, as well as two teachers and one class of fifth-grade elementary school students to assess the practicality aspect. Data were collected through validation sheets, teacher and student response questionnaires, and observations. The data were analyzed using descriptive quantitative techniques by calculating the mean score of each assessment aspect to determine the level of validity and practicality of the media. The results show that the digital Flipbook media achieved good to very good categories in aspects of display, graphics, safety, content suitability, and practicality, with an average score of 3.8. Furthermore, the practicality test indicates that the media is easy to use, has clear instructions, is engaging, and is efficient in supporting the learning process. Qualitative findings also reveal that the use of the media increases student engagement and facilitates understanding of intrinsic elements of stories.